Hubungan Pola Komunikasi Pimpinan Terhadap Kinerja Pegawai Dalam Novel Resign Karya Almira Bastari - Leonardus Leonardus; Aulia Rahman ; Eva Dwi Kurniawan (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Communication patterns are one of the important factors that influence employee performance. The right communication pattern will be able to encourage employees to work more and be more productive, so that they can achieve organizational goals. This research is a type of qualitative research with descriptive methods. The data in this statement comes from the novel Resign by Almira Bastari. The novel Resign by Almira Bastari tells the story of the life of an employee named Alranita who works in a consulting office in Jakarta. Alranita experienced various difficulties in her work, one of which was due to her boss's authoritarian leadership style. The communication patterns established by the leadership in the company caused Alranita to feel uncomfortable and unmotivated at work. Based on the analysis of the novel Resign, it can be concluded that communication patterns have a negative influence on employee performance. As a result, employees become less productive and their performance decreases. Therefore, it is important for leaders to understand the application of appropriate communication patterns. Leaders must be able to create a conducive and supportive work environment, so that employees can work comfortably and are motivated.